(untitled) (Research, Society and Development, 2022)
This article addresses the use of digital educational objects as a field of interrelation between education and digital technologies, turning scientific knowledge into an object of knowledge to be taught. The text points out the importance of educational products produced in the perspective of Vocational and Technological Education for the broad and integral formation of the student in high school. In order to do so, the conceptualization and understanding of digital educational objects and the theory of digital technological didactic transposition in education were sought through bibliographic research. A data analysis was also carried out through the results obtained by the bibliographic review of scientific publications (dissertations/educational products) published on the web page of the Masters in Professional and Technological Education of the IFTO - Campus Palmas. A brief discussion was also raised on the use of digital technologies in education as a possible resource for the broad and comprehensive training of young people today. In its conclusion, the article reveals that the various digital educational objects produced enable guiding paths in the teaching and learning process.